Assistance with the Implementation of the Independent Curriculum in Building Pancasila Student Profiles for School Principals and Driving Teachers: Pendampingan Implementasi Kurikulum Merdeka (IKM) dalam Membangun Profil Pelajar Pancasila bagi Kepala Sekolah dan Guru Penggerak - Diding Nurdin; Suryadi, Suryadi; Uum Murfiah; Arip Amin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Assistance in the Implementation of the Independent Curriculum (IKM) in Building Pancasila Student Profiles for School Principals and Driving Teachers. The assistance of school principals and driving teachers is a form of community service activity. The aim of implementing this activity is to provide assistance to the elementary school teacher working group in designing the annual work program. The mentoring method used uses the GROW Coaching Model approach which consists of 4 main stages, namely Grow, Reality, Options, and Will. The subjects of this activity are school principals and elementary school driving teachers in the Garut district education office area. Data obtained from this research will be analyzed to identify changes in participants' understanding and skills related to the Merdeka Curriculum and the development of Pancasila student profiles. It is hoped that the research results will provide insight into the effectiveness of the GROW method in supporting the implementation of the Merdeka Curriculum, as well as provide recommendations for stakeholders in the education sector to increase understanding and application of Pancasila values in the educational context